Risk factors of S. aureus intramammary infection in pre partum dairy heifers under grazing conditions and molecular characterization of isolates from heifers and cows - Camussone, Cecilia (2020)
The aims of the research reported here were to identify potential risk factors associated with the presence of Staphylococcus aureus intramammary infection (IMI) in pre partum dairy heifers on 17 dairy farms from three provinces of Argentina and to characterize, at molecular level, isolates from those heifers and lactating cows from two selected herds. A total of 1474 heifers and 4878 lactating cows were studied. The prevalence of Staphylococcus aureus IMI in the heifers, heifers at quarter level and lactating cow mammary quarters was 14.41, 4.82, and 14.65%, respectively. Univariate analysis showed the key variables associated with S. aureus IMI presence in the heifers were: S. aureus IMI prevalence in cows of the lactating herd, the time calves stayed with their dam after birth, the calf rearing system, the place of rearing (own farm or other dairy farm) and fly control on the farm. None of the variables included in the multivariable analysis was associated with the presence of S. aureus IMI in the pre partum heifers, probably due to low variability among management practices used by the farms for rearing the heifer calves. At the molecular level, S. aureus isolates were grouped into three main PFGE clusters and several genotypes within the clusters. Isolates from mammary secretion of pre partum heifers and milk of lactating cows comprised different PFGE clusters in both herds, although two exceptions occurred. The absence of gene fnbpB, which codifies for a virulence factor protein involved in cell invasion by S. aureus, was significantly more frequent in pre partum heifer secretion isolates than in isolates from lactating cow milk. These results suggest that, under these management conditions, isolates from mammary secretions of pre partum heifers do not originate from the milk of lactating cows, but rather other sources to which the heifer is exposed.